Hamilton Receptor‐Mediated Self‐Assembly of Orthogonally Functionalized Au and TiO2 Nanoparticles - Ali, Muhammad; Hasenöhrl, Dominik; Zeininger, Lukas; Muellner, Alexander R. M.; Peterlik, Herwig; Hirsch, Andreas (Helvetica Chimica Acta, 2019)
A new prototype of reversible self-assembly between functionalized gold and titanium dioxide nanoparticles (NPs) utilizing hydrogen bonding interactions was developed and established. The gold nanoparticles were functionalized with a Hamilton-receptor functionality bearing a thiol moiety as anchoring group. The titanium dioxide nanoparticles were modified with cyanurate derivatives which contained phosphonic acids as anchoring groups. The host–guest type interaction between two functionalized nanoparticles yielded a highly integrated nanoparticle system in chloroform. Moreover, by presenting a competing ligand in an exchange reaction, the product of self-assembly can be segregated into the individual soluble components of functionalized nanoparticles. The self-assembly and the exchange reaction were followed and monitored in detail by UV/Vis spectroscopy. The structure of the self-assembly product was investigated using scanning electron microscopy (SEM) and small-angle X-ray scattering (SAXS).
CRIS-Team Scopus Importer:2019-05-02
Keywords: gold; Hamilton receptors; nanoparticles; surface modification; self-assembly; titanium dioxide

Hierarchical Assembly and Sensing Activity of Patterned Graphene-Hamilton Receptor Nanostructures - Bao, Lipiao; Zhao, Baolin; Ali, Muhammad; Assebban, M'hamed; Yang, Bowen; Kohring, Malte; Ryndyk, Dmitry A.; Heine, Thomas; Weber, Heiko B.; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2022)

Host-Guest Systems on the Surface of Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) Utilizing Hamilton Receptors and Cyanurate Derivative Molecules - Ali, Muhammad; Kataev, Evgeny; Müller, Johannes; Park, Hyoungwon; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2021)
The study of hydrogen bonding interactions at the level of functionalized nanoparticles remains highly challenging and poorly explored area. In this work, superparamagnetic iron oxide nanoparticles (SPIONs) were orthogonally functionalized using receptors bearing multiple hydrogen bonding motifs. Pristine SPIONs were modified by wet chemical processes with Hamilton receptors (hosts), or cyanurate-guest molecules linked to phosphonic acid moieties for monolayer functionalization. The modified surfaces were fully characterized and the number of attached ligands on the surface were determined. The host-guest interactions on the interface of modified SPIONs were investigated by using UV-Vis spectroscopic titrations. Functionalized SPIONs demonstrated two to three magnitudes stronger binding affinities as compared to the related molecular interactions in solution due to synergistic effects on complex surface environment. Higher supramolecular binding ratios of host-guest interactions on the modified surface were emerged. These studies provide fundamental insights into supramolecular complexations on the surface at solid-liquid interface systems with applications in engineered nanomaterials, nano-sensing devices, and drug delivery systems.
CRIS-Team Scopus Importer:2021-11-05
Keywords: artificial hydrogen bonds; functionalized nanoparticles; hamilton receptors; host-guest chemistry; SPIONs